A Method for the Layer Compression Test Considering the Anisotropic Material Behavior - Merklein, Marion; Kuppert, Andreas (International Journal of Material Forming, 2009)
The layer compression test is used in the field of material characterization to determine the onset of yielding and the hardening behavior of a sheet metal within uniaxial compression loading. For testing anisotropic materials the experimental setup has to be adjusted and the evaluation has to be adapted. This could be achieved with the installation of a second optical strain measurement system to get data of both symmetry axes. In the following paper the experimental procedure with two strain measurement systems and the evaluation methodology regarding the two sets of data will be presented and validated with experimental results. The advantage of the layer compression test is discussed in comparison with the results of a standard tensile test. © Springer/ESAFORM 2009.
LFT Import::2019-08-05 (292)
Keywords: Anisotropy; Layer compression test; Material characterization